2005
DOI: 10.1007/s10562-005-4904-4
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of β-Glucosidase on carbon nanotubes

Abstract: Carbon nanotubes are demonstrated as a good support for the immobilization of b-Glucosidase. This is an enzyme with high molecular weight (ca. 135 kDa). A high enzyme loading of 630 mg per gram of support was achieved in 12 h. The link between the enzyme and the carbon nanotubes surface was by electrostatic interactions due to the different charges of the enzyme and the support at the pH of the immobilization. Immobilized b-Glucosidase showed a catalytic activity above 400 U/g on the hydrolysis of 4-nitropheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 21 publications
(18 reference statements)
1
24
0
2
Order By: Relevance
“…Both approaches have their advantages and shortcomings [3][4][5][6]. The advantage of adsorption is simplicity, as usually no cross-linking reagents or activation steps are required.…”
mentioning
confidence: 99%
“…Both approaches have their advantages and shortcomings [3][4][5][6]. The advantage of adsorption is simplicity, as usually no cross-linking reagents or activation steps are required.…”
mentioning
confidence: 99%
“…It is worth noting that even physical adsorption of enzymes onto carbon surfaces may induce secondary structural perturbations as a result of protein interaction with the carbon surface, 495 and that substantial perturbation can induce either nearly complete loss 505 or significant increases 506,507 in catalytic activity. Structural and biochemical characterization have revealed that the curvature of the carbon nanomaterial affects the immobilization yield, the catalytic behavior and the secondary structure of enzymes.…”
Section: Cnts For Enzyme Immobilizationmentioning
confidence: 99%
“…507 Recent works have also emphasized biocatalysis with carbon nanomaterials for enzyme-based biofuel cells, 525 and encouraging results have been reported on the use of enzyme-nanocarbon composites for electrocatalytic H 2 oxidation, 526,527 oxygen reduction 528 , glucose oxidation, 529,530 or ethanol oxidation. 531 In order to produce effective and recyclable catalysts for enantioselective trans-esterification in industrial applications, alkaline lipase from Pseudomonas fluorescens was non-covalently immobilized on pristine and oxidized MWCNTs.…”
Section: Cnts For Enzyme Immobilizationmentioning
confidence: 99%
“…8 They are increasingly attracting attention as the nano-scale materials for potential biological applications. [9][10][11][12][13][14][15][16] A useful type of applications is illustrated by their use as nano-scale supporters for immobilizing enzyme leading to biosensors and nanobiocatalysts. Carbon nanotubes, particularly single walled carbon nanotubes, have a large surface area, thus enabling the high loading of enzymes and lowering diffusional resistance.…”
Section: Introductionmentioning
confidence: 99%